Analysis of electrical responses of MEMS piezoresistive microcantilever - Ab Rahim, Rosminazuin; Ookar Abubakkar, Sheik Fareed; Bais, Badariah; Yeop Majlis, Burhanuddin (2014)
In this paper, an optimization of mechanical and electrical performance of single-layer silicon piezoresistive microcantilever (PRM) sensor in which both piezoresistor and microcantilever structures are made of the same material of single-crystalline silicon was discussed. Using CoventorWare 2008, the mechanical and electrical behaviors of the PRM structure was investigated by studying few contributing factors that affect the performance of the device. The performance of PRM sensor was investigated by observing the effects of applied loads to the current change and sensitivity of the device. Apart from that, the effects of thermal noise to the device’s performance were also investigated. From the simulation results, at applied loads between 1 to 10 µN, significant current increase of about 0.094% was observed. This current increase can be translated into an increase of sensitivity in the device. Simulation results also revealed that at temperature change between 290 K to 300 K, the PRM sensor shows insignificant change to sensitivity.